2019
DOI: 10.1039/c9cc04868e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed decarbonylative annulation of phthalimides with arynes: direct construction of phenanthridinones

Abstract: A novel palladium-catalyzed decarbonylative annulation between phthalimides and arynes was well-established, affording phenanthridinone derivatives in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Several methodologies have been reported in the literature for the synthesis of phenanthridinones via either transition metal catalysis (Pd, Rh, Cu) or radical-mediated catalysis either via C–C/C–N bond formation (I, III, IV) , or via aminocarbonylation/CO insertion (II) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Several methodologies have been reported in the literature for the synthesis of phenanthridinones via either transition metal catalysis (Pd, Rh, Cu) or radical-mediated catalysis either via C–C/C–N bond formation (I, III, IV) , or via aminocarbonylation/CO insertion (II) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out by Harmata et al on the preparation of benzofused benzothiazines from o -halo sulfoximines, they also reported Pd-catalyzed annulation examples, albeit in low yields . Recently, Meng, Xu, and co-workers achieved a Pd-catalyzed decarbonylative annulation of phthalimides 10-91 with o -silylaryl triflates, affording phenanthridinones 10-92 with good functional group tolerance (Scheme b) . Mechanistically, the catalytic cycle involves (1) oxidative addition of Pd(0) into an imide N–CO bond to generate intermediate 10-93 ; (2) decarbonylation to give a five-membered palladacycle 10-94 ; (3) aryne insertion to form a seven-membered palladacycle 10-95 ; and (4) reductive elimination to yield 10-92 along with the regeneration of Pd(0) species.…”
Section: Transition-metal-catalyzed Reactionsmentioning
confidence: 99%
“…Multinuclear NMR spectroscopy showed that other coordinating solvents such as MeCN or DMSO also gave adducts tentatively assigned as 7·NCMe and 7·DMSO , but these could not be isolated as crystalline solids. Diamagnetic Pd analogues are known. As shown in Scheme a), the C–H activation of 3 liberates 1 equiv of [AQ piv ]H ( 1a ), which was observed by 1 H NMR spectroscopy. The C–H activation 5 in the absence of added base also produced 1a , presumably because the t BuCO 2 H produced by deprotonation of the C–H bond protonates unreacted 5 , generating [AQ piv ]H ( 1a ), which lowers the yield.…”
Section: Results and Discussionmentioning
confidence: 98%